An early ABA-induced stomatal closure, Na+ sequestration in leaf vein and K+ retention in mesophyll confer salt tissue tolerance in Cucurbita species - Niu, Mengliang (Journal of experimental botany, 2018)
Tissue tolerance to salinity stress is a complex physiological trait composed of multiple 'sub-traits' such as Na+ compartmentalization, K+ retention, and osmotic tolerance. Previous studies have shown that some Cucurbita species employ tissue tolerance to combat salinity and we aimed to identify the physiological and molecular mechanisms involved. Five C. maxima (salt-tolerant) and five C. moschata (salt-sensitive) genotypes were comprehensively assessed for their salt tolerance mechanisms and the results showed that tissue-specific transport characteristics enabled the more tolerant lines to deal with the salt load. This mechanism was associated with the ability of the tolerant species to accumulate more Na+ in the leaf vein and to retain more K+ in the leaf mesophyll. In addition, C. maxima more efficiently retained K+ in the roots when exposed to transient NaCl stress and it was also able to store more Na+ in the xylem parenchyma and cortex in the leaf vein. Compared with C. moschata, C. maxima was also able to rapidly close stomata at early stages of salt stress, thus avoiding water loss; this difference was attributed to higher accumulation of ABA in the leaf. Transcriptome and qRT-PCR analyses revealed critical roles of high-affinity potassium (HKT1) and intracellular Na+/H+ (NHX4/6) transporters as components of the mechanism enabling Na+ exclusion from the leaf mesophyll and Na+ sequestration in the leaf vein. Also essential was a higher expression of NCED3s (encoding 9-cis-epoxycarotenoid dioxygenase, a key rate-limiting enzyme in ABA biosynthesis), which resulted in greater ABA accumulation in the mesophyll and earlier stomata closure in C. maxima